A Development of the Flipped Learning Model Using the Critical Inquiry Process to Enhance Research Skills - Kaeophanuek, Siriwatchana; Chookerd, Naparat (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Flipped Classroom’ has become more popular in higher education for encouraging self-learning enthusiasm. This research aims to propose a learning process model of flipped classroom to develop research skill by applying critical inquiry theory in the instructional design to develop thinking, finding answer and research skills which are the key competency for conducting a research. The research methodology was divided into two phases: the first phase included literature review to develop the learning process model, the second phase included learning model suitability evaluation by expert. The results showed that experts have strongly agreed with the learning model. We anticipate that our flipped classroom model which has divided into 3 phase included pre-class, in-class and after-class phases with the addition of thinking skill development activity by using critical inquiry technics could be used for reference for teachers on planning and implementing instructional activities to enhance the research skill of undergraduate students